Gradual damage evolution and propagation in quasi-isotropic CFRC under quasi-static loading. (1st February 2018) - Tessema, Addis; Ravindran, Suraj; Kidane, Addis
Abstract: The gradual damage initiation and evolution in quasi-isotropic (±45, 90, 0)s carbon fiber laminate composites under a quasi-static tension loading is investigated experimentally. The full-field strains across the thickness of the laminate as a function of applied tensile load was acquired using high spatial resolution digital image correlation. The chnage in strain during the initiation and growth of micro-cracks is evaluated, and the influence of strain redistribution over the surrounding layers is analyzed. The local failure mechanism is investigated and the influence of the local damage on the global mechanical response of the composite is explored. It was found that the failure is initiated as a matrix crack in the most off-axis plies, gradually propagate to the nearby ply and eventually grow to a complete delamination. Further, it was found that the shear lagging induced between two adjacent plies has a significant effect in directing the matrix crack growth and inducing delamination.